Utilization of Facebook as a Media for Preaching for Islamic Communication and Broadcasting Students at the Al-Amin Islamic College (STAI) Dompu NTB - Akbar, Ferry; Miskan Miskan; Firmansyah, Firmansyah (JURNAL PENDIDIKAN IPS, 2025)
The study aims to examine how to utilize Facebook social media as a medium for preaching for Islamic Communication and Broadcasting students at the Al-Amin Islamic College (STAI) Dompu NTB. This research is a qualitative descriptive study. Data collection techniques through observation, interviews and documentation. This type of research is descriptive qualitative using a communication approach. The data sources used are primary data and secondary data. Data collection methods used are observation, interviews, and documentation. Data processing and analysis techniques are carried out through three stages, namely: reducing data (data reduction), presenting data (data display), and drawing conclusions (verification). The results of this study indicate that the use of Facebook as a medium for preaching for students of the Islamic Communication and Broadcasting Study Program at the Al-Amin Islamic College of Dompu includes: 1. Disseminating Islamic content. The dissemination of Islamic content has an important role in shaping the character of Muslims to be better, inspiring goodness, and becoming an effective means of preaching in the modern era. 2. Live streaming of Islamic studies and lectures. Through this live broadcast or live streaming, KPI STAI Al-Amin Dompu students can provide events such as religious lectures, Islamic discussions, and even direct Q&A with the general public and fellow students. 3. Create a Dakwah Group or Page. Facebook groups or can be used for discussions, sharing experiences, and answering religious questions. 4. Distributing Islamic Videos. By using Facebook groups or pages, Islamic messages can be disseminated quickly, providing inspiration and knowledge to many people, and strengthening the community in practicing religious teachings, especially Islam in Dompu Regency. 5. Disseminating Information on Religious Activities. Islamic communication and broadcasting students of STAI Al-Amin Dompu in socializing religious activities, especially those in Dompu Regency, are by disseminating them through Facebook.